Eficiencia de carbón activado procedente del coco (Cocos nucifera) en remoción de sólidos en aguas residuales de la empacadora de pescado FRESCODEGFER - Mendoza Moreira, Mauricio Alexander (2019)
The objective of the investigation was to evaluate the efficiency of activated carbon from the coconut shell (Cocos nucifera) in the removal of solids from the wastewater of the FRESCODEGFER fish baler. The experiment was conducted under a completely randomized design with three replicates and three treatments T1 (25g), T2 (50g) and T3 (100g) of activated carbon. The sample was taken in situ in the tributary, collecting 10 liters of wastewater for the total analysis, controlling the temperature conditions. Physical analyzes were carried out on the water such as: suspended solids, turbidity, color and pH. In the characterization of the physical parameters of the wastewater, 90 mg / l of SST, 200 NTU of turbidity, 433 Pt / Co of color and a pH of 7.22 were obtained. The removal percentages resulting from the parameters evaluated were processed in the Statgraphics statistical software, to perform the analysis of variance and Tukey test. In the variable total suspended solids, the T1 treatment removed 52%, being the most efficient, in the T3 treatment the turbidity variables with 29% and color with 12% reached a high removal; validating the research hypothesis, because there was a significant difference between treatments by variables.